A new interpretation of the structure and solvent dependence of the far UV circular dichroism spectrum of short oligopeptides. Issue 40 (29th April 2019) - Kumar, Anshuman; Schweitzer-Stenner, Reinhard; Wong, Bryan M.
Abstract : Classical excitonic models are unsuitable for describing the electronic structure of polypeptides, and explicit consideration of water is essential. Abstract : UV circular dichroism (UVCD) spectroscopy is a prominent tool for exploring secondary structures of polypeptides and proteins. In the unfolded state of these biomolecules, most of the individual residues primarily sample a conformation called polyproline II. Its CD spectrum contains a negatively biased positive couplet with a pronounced negative maximum below and a weak positive maximum above 200 nm. It is traditionally rationalized in terms of an excitonic coupling mechanism augmented by polarization effects. In this work, we carry out new time-dependent density functional theory calculations on the cationic tripeptide GAG in implicit and explicit water to determine the transitions that give rise to the observed CD signals of polyproline II and β-strand conformations. Our results reveal a plethora of electronic transitions that are governed by configurational interactions between multiple molecular orbital transitions of comparable energy. We also show that reproducing the CD spectra of polyproline II and β-strand conformations requires the explicit consideration of water molecules. The structure dependence of delocalized occupied orbitals contributes to the experimentally-observed invalidation of Flory's isolated pair hypothesis.